2021
DOI: 10.1108/jhti-09-2020-0165
|View full text |Cite
|
Sign up to set email alerts
|

Virtual site visits for meeting and event planning: are US convention facilities ready?

Abstract: PurposeThis study aims to explore virtual site visit adoption patterns of US convention facilities based on the diffusion of innovation (DOI) theory. Additionally, it offers predictive models of virtual site visit tool adoption by applying probability distributions.Design/methodology/approachThe study used content analysis of 369 US convention facility websites. Data collected from the websites recorded the presence or absence of the following tools facilitating virtual site visits: photos, floor plans, videos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 53 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…With all the proposed benefits of VR applications, it is notable that convention centers have shown to be slow to adopt this technology in their sales and marketing efforts and for site visits. For example, a study conducted at the beginning of the COVID-19 pandemic showed that over 70% of convention center websites utilized floor plans and photos to provide information for prospective clients, while under 20% percent employed 360-degree tours and videos, and only approximately 4% offered a VR-optimized tour (Soifer et al, 2021).…”
Section: Meetings and Events Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…With all the proposed benefits of VR applications, it is notable that convention centers have shown to be slow to adopt this technology in their sales and marketing efforts and for site visits. For example, a study conducted at the beginning of the COVID-19 pandemic showed that over 70% of convention center websites utilized floor plans and photos to provide information for prospective clients, while under 20% percent employed 360-degree tours and videos, and only approximately 4% offered a VR-optimized tour (Soifer et al, 2021).…”
Section: Meetings and Events Industrymentioning
confidence: 99%
“…Convention centers use different media to showcase the facility and communicate vital information to meeting and event planners on their websites: photos, floor plans, videos, 360-degree photos and videos, and VR-optimized tours (Soifer et al, 2021). Boyd and Koles (2019) proposed the following definition of VR:…”
Section: Introductionmentioning
confidence: 99%
“…The third paper by Soifer et al (2021) is entitled “Virtual site visits for meeting and event planning: are US convention facilities ready?”. This timely study examined the rate of VR and other technologies adopted by convention facilities to enable virtual site visits.…”
Section: The Papers In This Issuementioning
confidence: 99%